Sistem Informasi Pengelolaan Event Kampung Budaya Polowijen - Pratama, Ade Ramadhana; Anita, Anita; Widodo, Sugeng (J-INTECH (Journal of Information and Technology), 2022)
The Polowijen Cultural Village is a cultural area that preserves various traditional cultures such as mask dances, mask making, batik and the preservation of indigenous polowijen culture and sites. Through its website, the Polowijen cultural village attracts tourists and investors to visit or propose organizing cultural arts activities. Currently, event management is carried out by recording in a book and centered on the personal mover. Some of the problems that arise from the management carried out are the difficulty of scheduling activities when the number of submissions is more than usual, event submissions are not served because the records are piled up and the management of donations and payment administration has not been managed optimally. The purpose of this research is to design and build an information system that can assist managers in the process of submitting events, payments, validation of submissions and payments and management of donations. System users are cultural village managers, tourists and donors. The system is built on a web-based with mysql as the database management System. Based on the results of trials using the black box method, the information system that was built was in accordance with the design and was in accordance with the needs of the cultural village so that system users would have convenience in managing events and being able to overcome existing problems.